2021
DOI: 10.1002/jat.4242
|View full text |Cite
|
Sign up to set email alerts
|

Iodine excess induces hepatic, renal and pancreatic injury in female mice as determined by attenuated total reflection Fourier‐transform infrared spectrometry

Abstract: Limited knowledge of the long‐term effects of excessive iodine (EI) intake on biomolecular signatures in the liver/pancreas/kidney prompted this study. Herein, following 6 months of exposure in mice to 300, 600, 1200 or 2400 μg/L iodine, the biochemical signature of alterations to the liver/pancreas/kidney was profiled using attenuated total reflection Fourier‐transform infrared (ATR‐FTIR) spectroscopy coupled with principal component analysis‐linear discriminant analysis (PCA‐LDA). Our research showed that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Furthermore, the deficiency or excessive consumption of iodine has been associated with the risk of presenting insulin resistance [9]. Similarly, in our study, excess iodate caused high insulin levels and a decrease in IR, which correlates with other studies that show that low levels insulin levels and low levels of IR are associated with pancreatic fibrosis, insulin resistance, and alterations in insulin gene regulation [3,4,[7][8][9][10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the deficiency or excessive consumption of iodine has been associated with the risk of presenting insulin resistance [9]. Similarly, in our study, excess iodate caused high insulin levels and a decrease in IR, which correlates with other studies that show that low levels insulin levels and low levels of IR are associated with pancreatic fibrosis, insulin resistance, and alterations in insulin gene regulation [3,4,[7][8][9][10].…”
Section: Discussionsupporting
confidence: 90%
“…In murine models, the consumption of 3.5 mg of potassium iodide (KI)/100 g body weight, which is 500 times the physiological daily dosage of iodide, for 60 days causes a hyperglycemic and hypercholesteremic status and severe destruction of the pancreatic structure [9]. In mice, the excessive consumption of 1200 or 2400 µg/L of iodide alters insulin, blood glucose levels, and the homeostasis model assessment for insulin resistance (HOMA-IR) index after 6 months [10]. In contrast, low iodine and 25(OH)D concentrations have been associated with complications in diabetic patients [8], and excessive consumption of iodine is associated with pancreatic damage in epidemiological studies [3][4][5][6][7]11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive iodine intake is associated with thyroid disease; however, research on the association between urinary iodine and NAFLD is lacking. However, some studies have suggested that excessive iodine consumption may disrupt the structure, metabolism, and function of cell membranes, potentially leading to liver, kidney, and pancreatic damage ( 32 ). This disruption could explain the non-linear dose-dependent relationship observed here between I levels and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Second, chronic inflammatory states and oxidative stress appear to be central to the pathophysiology of MetS. Excess iodine puts cells in a state of high oxidative stress, which predisposes them to organ damage and is detrimental to disease recovery ( 59 ). Moreover, iodine functions as both a pro-oxidant and an antioxidant ( 60 , 61 ), and it can balance oxidative homeostasis at the physiological and molecular levels of the cell ( 62 ).…”
Section: Discussionmentioning
confidence: 99%